The Antifungal Plant Defensin HsAFP1 from Heuchera sanguinea Induces Apoptosis in Candida albicans - Aerts, An M.; Bammens, Leen; Govaert, Gilmer; Carmona-Gutierrez, Didac; Madeo, Frank; Cammue, Bruno P.; Thevissen, Karin (Frontiers in Microbiology, 2011)
Plant defensins are active against plant and human pathogenic fungi (such as Candida albicans) and baker’s yeast. However, they are nontoxic to human cells, providing a possible source for treatment of fungal infections. In this study, we characterized the mode of action of the antifungal plant defensin HsAFP1 from coral bells by screening the Saccharomyces cerevisiae deletion mutant library for mutants with altered HsAFP1 sensitivity and verified the obtained genetic data by biochemical assays in S. cerevisiae and C. albicans. We identified 84 genes, which when deleted conferred at least 4-fold hypersensitivity or resistance to HsAFP1. A considerable part of these genes were found to be implicated in mitochondrial functionality. In line, sodium azide, which blocks the respiratory electron transport chain, antagonized HsAFP1 antifungal activity, suggesting that a functional respiratory chain is indispensable for HsAFP1 antifungal action. Since mitochondria are the main source of cellular reactive oxygen species (ROS), we investigated the ROS-inducing nature of HsAFP1. We showed that HsAFP1 treatment of C. albicans resulted in ROS accumulation. As ROS accumulation is one of the phenotypic markers of apoptosis in yeast, we could further demonstrate that HsAFP1 induced apoptosis in C. albicans. These data provide novel mechanistic insights in the mode of action of a plant defensin.